Facile synthesis of stilbene-derivatized Schiff base ligands and their Cu(II) complexes - Uehara, D.; Salas, P. (Elsevier, 2023)
Herein we present the synthesis and characterization of three Schiff base ligands derivatized with stilbene groups and their Cu(II) complexes CuL1-3, prepared in only three synthetic steps, from simple aromatic rings to complexes. The ligands L1-3 were synthesized first by the Csingle bondC coupling of an aryl bromide and styrene via a Heck reaction to produce a stilbene and then, by a condensation reaction between the stilbene and an aliphatic diamine to form tetradentate Schiff base ligands L1-3. CuL1-3 were then easily formed by complexation of Cu(II) ion in ethanolic media and obtained pure and in high yields. The complexes, ligands, and intermediates were fully characterized using FTIR, UV–vis, and NMR spectroscopy, as well as HRMS and XRD. These compounds exhibit two stilbene units, a functional group that has shown high affinity for amyloid plaques, an important biomarker of Alzheimer’s disease. Thus, these compounds have the potential to be studied as radioimaging agents for the diagnosis of Alzheimer's by positron emission tomography (PET) when prepared with the positron-emitting radioisotope Cu-64.
Keywords: Chemistry; Schiff base; Bromide; Styrene; Condensation reaction; Polymer chemistry; Ligand (biochemistry); Proton NMR; Combinatorial chemistry; Diamine; Heck reaction; Nuclear magnetic resonance spectroscopy; Aryl; Organic chemistry; Alkyl; Polymer; Copolymer; Catalysis; https://purl.org/pe-repo/ocde/ford#1.04.01